The oxygen uptake efficiency slope does not accurately predict V˙O2peak of children – the Arkansas Active Kids study - Edwards, Timothy; Børsheim, Elisabet; Weber, Judith L.; Diaz, Eva C. (Frontiers in Physiology, 2024)
Background Cardiorespiratory fitness (CRF) is a vital indicator of health. However, accurately measuring peak oxygen consumption (V˙O2peak) to determine CRF in children can be challenging. The oxygen uptake efficiency slope (OUES) has been proposed as an alternative metric for predicting V˙O2peak in children, but its accuracy and agreement with measured V˙O2peak remain unclear. Methods A post hoc analysis was conducted in 94 children (ages 7–10 years) who completed an incremental cycle ergometer test to measure V˙O2peak. Body composition (Dual-energy X-ray absorptiometry) was measured, and fat mass index (FMI, kg/m2) and fat-free mass index (FFMI, kg/m2) were calculated. OUES was determined using all respiratory data (OUES100%) collected during the cycle ergometer test and using data only up to 60% of heart rate reserve (OUES60%HRR). Regression equations to predict V˙O2peak (Pred-V˙O2peak) were derived from simple and multiple linear regression analysis. Bland-Altman analysis assessed the level of agreement between Pred-V˙O2peak and measured V˙O2peak. Results OUES60%HRR (β = 0.46, p < 0.0001), age (β = 56.0, p = 0.0004), White race (β = 173.3, p < 0.0003), FFMI (β = 0.98.6, p < 0.000), and FMI (β = −0.40.8, p < 0.000) were retained in the final model. The difference between measured V˙O2peak and Pred-V˙O2peak was not different from zero (p = 0.999). There was a positive association between the difference of measured V˙O2peak and Pred-V˙O2peak and the average of the two methods (β = 0.79, p = 0.0028). Conclusion There was no mean bias between measured V˙O2peak and Pred-V˙O2peak. However, magnitude bias was present even after considering other significant predictors of V˙O2peak (FMI, FFMI, race, and age) in the regression equation. Caution is advised when using OUES to predict V˙O2peak in children.